Rancang Bangun Pembangkit Listrik Photovoltaic 8x10 Wp Menggunakan Buck Converter Berbasis Arduino Sebagai Penggerak Motor Pompa - Simarmata, Arjuna; Rajagukguk, Antonius (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
A photovoltaic (PV) system cannot generate maximum power automatically. The most important problems in solar technology are low conversion efficiency and the presence of I-V characteristics that are highly non-linear depending on solar radiation. To extract the maximum power, the PV array must be able to track changing maximum power points. Therefore, we need a method in order to obtain the maximum power generated by PV. In this study the author discusses the method of optimizing PV power using Maximum Power Point Tracking (MPPT) with the Perturbation & Observation (P&O) algorithm and Buck converter. The P&O algorithm is a method for tracking the highest power point generated by PV. The design was tested into four case, namely case, with no solar radiation, cloudy case, bright case, and very bright case. The design of the PV generator is used to charge 12 volt DC batteries and serve the 12 volt water pump motor. The battery charging process lasts for 4 hours. Building design test with pump motor load is carried out for 4 hours. The power consumed by the pump motor is 10 watts to 14 watts and the total water transferred by the water pump motor is 3188 liters. Keywords : Solar Cell, Buck converter, MPPT, Arduino